Enhancement of safflower productivity through improved production technology: Enhancement of safflower productivity through improved production technology - P O BHUTADA,; S A SHIND,; S B GHUGE, (Journal of Oilseeds Research, 2023)
Experiment was conducted at Research farm of AICRP on Safflower Research scheme, VNMKV, parbhani. Experiment was conducted in un-replicated manner on 2000 sq. m area of improved technology and farmers’ practice each. Experiment on production potential of and economic effect of improved technologies comprising high yielding PBNS-12 during rabi 2021-22 under residual soil moisture conditions. The additional yield under improved technologies over local practice recorded 1540 kg/ha. In comparison to local practice, there was an increase of 32%. The improved technology with high yielding varieties also resulted in higher benefit cost: ratio of 2.58 with addition returns i.e. Rs. 20736/- over farmer practice.